Accelerated dual dynamic integer programming applied to short-term power generation scheduling - Santos, Kenny Vinente dos; Colonetti, Bruno; Finardi, Erlon Cristian; Zavala, Victor M. (International journal of electrical power & energy systems, 2023)
•Use of Dual Dynamic Integer Programming framework.•Inclusion of multiperiod stages and overlapping strategies to accelerate the method.•Solving the Short-Term Power Generation Scheduling problem.•Validation of the proposed scheme on the IEEE 118-bus system. The short-term generation scheduling (STGS) problem defines which units must operate and how much power they must deliver to satisfy the system demand over a planning horizon of up to two weeks. The problem is typically formulated as a large-scale mixed-integer linear programming problem, where off-the-shelf commercial solvers generally struggle to efficiently solve realistic instances of the STGS, mainly due to the large-scale of these models. Thus, decomposition approaches that break the model into smaller instances that are more easily handled are attractive alternatives to directly employing these solvers. This paper proposes a dual dynamic integer programming (DDiP) framework for solving the STGS problem efficiently. As in the standard DDiP approach, we use a nested Benders decomposition over the time horizon but introduce multiperiod stages and overlap strategies to accelerate the method. Simulations performed on the IEEE-118 system show that the proposed approach is significantly faster than standard DDiP and can deliver near-optimal solutions.